2016
DOI: 10.1161/jaha.115.002257
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Nitric Oxide Synthase Restores Circulating Angiogenic Cell Function in Patients With Coronary Artery Disease: Implications for Autologous Cell Therapy for Myocardial Infarction

Abstract: BackgroundCirculating angiogenic cells (CACs) are peripheral blood cells whose functional capacity inversely correlates with cardiovascular risk and that have therapeutic benefits in animal models of cardiovascular disease. However, donor age and disease state influence the efficacy of autologous cell therapy. We sought to determine whether age or coronary artery disease (CAD) impairs the therapeutic potential of CACs for myocardial infarction (MI) and whether the use of ex vivo gene therapy to overexpress end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…A previously published study by our lab found that psychological stress was associated with reduced migratory and paracrine function of CACs (a cell culture model containing CPCs) in vitro (19). In vitro CAC function is highly correlated with vascular repair capacity in vivo (49). The effects of stress on cell-mediated vascular repair in vivo could be tested by isolating human CACs or CD34 + cells from high versus low-stress healthy adults, and transplanting them into an animal model of vascular injury (49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previously published study by our lab found that psychological stress was associated with reduced migratory and paracrine function of CACs (a cell culture model containing CPCs) in vitro (19). In vitro CAC function is highly correlated with vascular repair capacity in vivo (49). The effects of stress on cell-mediated vascular repair in vivo could be tested by isolating human CACs or CD34 + cells from high versus low-stress healthy adults, and transplanting them into an animal model of vascular injury (49).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro CAC function is highly correlated with vascular repair capacity in vivo (49). The effects of stress on cell-mediated vascular repair in vivo could be tested by isolating human CACs or CD34 + cells from high versus low-stress healthy adults, and transplanting them into an animal model of vascular injury (49). …”
Section: Discussionmentioning
confidence: 99%
“…The current study provides a foundation to test stress pathways using human-to-animal CAC transplant models of vascular repair (e.g., post-myocardial infarction or leg ischemia)(Sonnenschein et al, 2011; Chen et al, 2016). For example, a previous study of patients with metabolic syndrome demonstrated that exercise improved the ability of these patients’ CACs to repair a carotid endothelial injury in vivo in a nude mouse model (Sonnenschein et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…CAC migration in vitro reflects the capacity of CACs to migrate toward sites of tissue damage and promote repair via paracrine secretion of growth factors. CAC migration is decreased in patients with coronary artery disease (Vasa et al, 2001), atherosclerosis (Ohtsuka et al, 2013), diabetes (Thum et al, 2007), and older age (Chen et al, 2016). Among healthy individuals without cardiovascular disease or diabetes, reduced CAC migration prospectively predicts greater carotid artery intima-media thickness (Keymel et al, 2008) and correlates with metabolic risk factors (Aschbacher et al, 2012a) and better endothelial function (Van Craenenbroeck et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, NOS3 is responsible for synthesising circulating NO and plays a crucial role in the pathogenesis of CAD 4 5. Chen et al 4 demonstrated that the mRNA and protein levels of NOS3 were significantly decreased in patients with CAD as compared with healthy subjects, and overexpression of NOS3 increased NO production and restored cardiac function after myocardial infarction in mice. In a mouse model of arterial restenosis, the antirestenotic effect of liraglutide was completely abolished by N-omega-nitro-L-arginine methyl ester, an inhibitor of NOS3 5…”
Section: Introductionmentioning
confidence: 99%